Forensic Examination and Criminalistics in Investigating War Crimes: European and Ukrainian Experiences - Shevchuk, Viktor; Zhuravel, Volodymyr; Yevdokimenko, Svetlana; Yevdokimenko, Serhii; Myshkov, Yaroslav (Jurnal Media Hukum, 2000)
The rising prevalence of war crimes, particularly in Ukraine, highlights the urgent need for robust forensic investigations to uphold justice and accountability in conflict zones. This study addresses the challenges in investigating war crimes, focusing on integrating effective forensic and criminalistics practices into Ukraine’s framework. The research aims to summarize best practices in forensic science by drawing on the experiences of European countries and their application in Ukraine. A structural-functional approach was employed, utilizing qualitative data from case studies, legal documents, and forensic reports. Comparative analysis of methods used in Ukraine and Europe highlights current investigative practices' successes and challenges. Key findings include the effectiveness of DNA analysis for victim identification, digital technologies for documenting crimes, and forensic methodologies in evidence collection and analysis. The study concludes that forensic science and criminalistics are indispensable in war crime investigations, emphasizing the adoption of innovative techniques to improve justice delivery. Integrating advanced forensic practices into Ukraine’s investigative processes can enhance accountability and contribute to international standards in war crime investigations.